2005
DOI: 10.1016/j.laa.2005.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of minimal polynomial bases: A generalized resultant approach

Abstract: We propose a new algorithm for the computation of a minimal polynomial basis of the left kernel of a given polynomial matrix F (s): The proposed method exploits the structure of the left null space of generalized Wolovich or Sylvester resultants to compute row polynomial vectors that form a minimal polynomial basis of left kernel of the given polynomial matrix. The entire procedure can be implemented using only orthogonal transformations of constant matrices and results to a minimal basis with orthonormal coe¢… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…One well-known example is the study of differential-algebraic equations (see for instance [7] and the references therein). Other sources of problems involving singular matrix polynomials are control and linear systems theory [22], where the problem of computing minimal polynomial bases of null spaces of singular matrix polynomials is still the subject of intense research (see [3] and the references therein for an updated bibliography). In this context, it should be noted that the matrix polynomials arising in control are often full-rank rectangular polynomials.…”
mentioning
confidence: 99%
“…One well-known example is the study of differential-algebraic equations (see for instance [7] and the references therein). Other sources of problems involving singular matrix polynomials are control and linear systems theory [22], where the problem of computing minimal polynomial bases of null spaces of singular matrix polynomials is still the subject of intense research (see [3] and the references therein for an updated bibliography). In this context, it should be noted that the matrix polynomials arising in control are often full-rank rectangular polynomials.…”
mentioning
confidence: 99%
“…Our algorithm is based on the LQ factorization and has a blocked formulation. We showed that it is more efficient than the similar algorithms presented recently in [23,24]. Moreover, in this paper we presented a full analysis of numerical stability and complexity.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the algorithm in [23] does not perform elementary polynomial operations, and the use of standard methods like the SVD improves numerical properties with respect to the classical polynomial methods. A similar work is presented in [24] using matrix resultants. We remark that both papers [23] and [24] appeared after submission of our conference papers [25,26], on which the present paper is based.…”
Section: Brief Review Of Existing Algorithmsmentioning
confidence: 97%
See 2 more Smart Citations